DO THE BIG FISH EAT THE LITTLE ONES? : ARTIFICIAL INTELLIGENCE VS. HUMANS IN TRANSLATING PROVERBS - Drahota-Szabó, Erzsébet (Proverbium - Yearbook, 2025)
This paper, with its provocative title, serves as a small experiment, a case study intended to spark further scholarly discussion. The central question is: Who handles the translation of proverbs more successfully – professional translators or ChatGPT? The author compares excerpts from Hungarian literary works with their German and English translations. Both human translations and those of generative artificial intelligence are critically analyzed. The source texts selected for the study contain proverbs that are constitutive of the text, i.e., they have a particular translation relevance. The primary evaluation criteria for analyzing the translations are: Who, the human or ChatGPT, can better assess the translation relevance of the respective proverb? Who can – based on translation relevance – choose an adequate translation procedure? In an exaggerated form, the question is whether or for how long translators (humans) are still needed when translating literary works.